Modeling the Energy Landscape of Side Reactions in the Cytochrome bc1 Complex - Husen, Peter; Solov’yov, Ilia A. (Frontiers in Chemistry, 2021)
Much of the metabolic molecular machinery responsible for energy transduction processes in living organisms revolves around a series of electron and proton transfer processes. The highly redox active enzymes can, however, also pose a risk of unwanted side reactions leading to reactive oxygen species, which are harmful to cells and are a factor in aging and age-related diseases. Using extensive quantum and classical computational modeling, we here show evidence of a particular superoxide production mechanism through stray reactions between molecular oxygen and a semiquinone substrate molecule bound in the mitochondrial complex III of the electron transport chain bc1 complex. Free energy calculations indicate a favorable electron transfer from semiquinone occurring at low rates under normal circumstances. Furthermore, simulations of the product state reveal that superoxide formed at the Qo-site exclusively leaves the bc1 complex at the positive side of the membrane and escapes into the intermembrane space of mitochondria, providing a critical clue in further studies of the harmful effects of mitochondrial superoxide production.